Fundamentals of Entrepreneurship ENT 300 : Krabba Hut / Mohd Shazwanie Faisal ... [et al.] - Faisal, Mohd Shazwanie; Tambi, Ahmad Luqman; Hanari, Arina Asyikin (2018)
The Krabba Hut is the partnership business that consist 3 partners where share the same interest and passion to do dishes that related to seafood homemade burger. The partners are consisting of general manager, marketing manager, financial manager, administration manager and operational manager. Furthermore, The Krabba Hut offers homemade burger with a twist of seafood patty and using waffle bun instead of regular homemade burger bun. As we all know, homemade burger are the fast food that everyone love to eat at any time they want especially during dinner. After a few discussions we have decided to open our shop at Kuching because of the high population in the Kuching area and the strategic place to open up the business. Jalan satok are one of the most used roads for Kuching citizen. Our shops are near to the shopping mall, residence area and offices. We expected to increase the number of customer and gain profit since we are the only shop that offers seafood waffle homemade burger in Kuching. Although Kuching has many competitors that sell homemade burger, we offer dishes that are different from any competitors so that we have the diversity of homemade burger. Our mission and vision are to make our business to expand and be well known in Kuching and other area or other state. We also hope that we can gain the maximum profit but minimize expenses.